Alkaloids and sulphur-containing amides from Glycosmis citrifolia and Glycosmis elongata - Rahmani, Mawardi; Muhammad Serang, Rosmiati; Mohd Hashim, Najihah; Md.Sukari, Mohd. Aspollah; Ee , Gwendoline Cheng Lian; Ali, Abdul Manaf; Mohd Ismail, Hazar Bebe (Universiti Kebangsaan Malaysia, 2010)
Air-dried leaves of both Glycosmis citrifolia and Glycosmis elongata collected from Bogor Botanical Garden, Indonesia were individually extracted with chloroform to give dark viscous extracts after solvent removal. Column chromatographic separation of the extract of G. citrifolia yielded 5(6)-glutene-3α-ol, two sets conformers(E)-dambullin and (Z)-dambullin, and (E)-methyldambullin and(Z)-methyldambullin. Similar treatment of the extract of G. elongatagave skimmianine and arborinine. The structures of the compounds were elucidated based on spectroscopic data and comparison with published reports.